De miliciano a comandante. La trayectoria miliciana de Agustín de Iturbide (1797-1813) (Tzintzun, Revista de Estudios Históricos, 2019)
The independence war catapulted the military career of some of the members of the novohispanic provincial militias, where it comes to the eye the case of Agustín de Iturbide. This viceregal officer, who entered to the kingÂ´s army in 1797, saw his military and political fame grew great during the first years of the war, whichearned him the designation as Commander of the GuanajuatoÂ´s province and the troops of the Bajío, with what he became one of the most important royal government officers.